BUSINESS DEVELOPMENT MODEL IN THE MICRO, SMALL AND MEDIUM ENTERPRISES AT TOURISM VILLAGE - Siti Arbainah; Hadiahti Utami; Sugiarti Sugiarti (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
The Micro, Small and Medium Enterprises (MSMEs) have an important role in economic development. It is reasonable if the empowerment of MSMEs gets special attention by the government, including MSMEs in tourism villages. The tourist village of Loram Kulon MSME which is one of the objects of this research is growing and diverse in both number and type. The diversity of MSMEs has resulted in village governments having difficulties in implementing MSME development programs that are in harmony with the characteristics of tourism villages. This study aims to formulate a business development strategy model for MSMEs in resource-based and local wisdom-based tourism villages. Except in the village of Loram Kulon, research has been carried out with the object of the Jambearum tourism village in Kendal Regency. The study used 7-10 samples of MSMEs taken randomly. Respondents are owners / managers of MSMEs. Data was collected through interviews with the help of questionnaires. Processed using descriptive statistics and analyzed quantitatively and qualitatively. From these two studies can be formulated a model of village tourism MSME development. The results show that the development model based on the SWOT analysis is the right model for formulating the tourism village MSME development strategy. This is because the SWOT analysis considers the internal and external conditions of MSMEs and provides four alternative strategies namely SO, ST, WO, WT which can be selected according to the general objectives of MSMEs in the tourism village